Armenian Press in the Context of Political and Cultural Processes of the Early 20th Century (Analytical Review) - Petrosyan, David (Bulletin of Yerevan University B: Philology, 2021)
The article attempts to present the general picture of the Armenian press at the beginning of the twentieth century, evaluating its contribution to the formation of the Armenian state at the beginning of the century, as well as to the formation of the Armenian cultural identity, in particular, in the formation of intercultural dialogue in society. Some principles of professional activity of the press are highlighted, which helped to re-evaluate the role of Armenian press in the public and political life of Armenia.
Keywords: Armenian press; statehood; cultural identity; thematic focus of the press; intercultural dialogue; editor of a periodical